Frequency of Self-Medication and Knowledge about Out-of-Counter Drugs during the COVID-19 Pandemic in a Group of Iranian Dental Students - Mehrnaz Karimi Afshar; Marzieh Karimi Afshar; Elham Abbaszadeh; Behnam Mahmood Molaei (Association of Support to Oral Health Research (APESB), 2023)
Objective: To study the frequency of self-medication and knowledge about out-of-counter drugs during the COVID-19 pandemic in a group of Iranian dental students. Material and Methods: A descriptive cross-sectional study was conducted among dental undergraduates from September 2021 to November 2021 after receiving ethical clearance from the Kerman Medical University Ethical Committee. A valid and reliable questionnaire, consisting of demographic data and questions about self-medication and knowledge about out-of-counter drugs, was sent to participants via E-mail. Data was analyzed by SPSS 26 software by using a t-test. The P-value was considered at a 0.05% significant level. Results: A total of 88 students participated in the study with a mean age of 21.39±3.71 years. Prevalence of self-medication was found in 53.4%. The most common cause for self-medication was headache. Acetaminophen was the most commonly used medicine for self-medication. Females had more self-medication than males, but there was no significant differences. There was no significant differences between entering year to university and self-medication. Younger students had significantly more self-medication (p=0.007). Knowledge about out-of-counter drugs was moderate. Conclusion: Moderate self-medication as noticed. The out-of-counter drugs were the most used. Although out-of-counter drugs seem relatively safe, their improper use can cause serious side effects. Dental students need to be educated regarding appropriate safe medication and out-of-counter drugs.